SCIENCE COMMUNICATION AND DISCURSIVE ETHOS: THE CREATION OF THE “BLUE MARBLE EARTH” - Salgado, Luciana Salazar; Marques, Joana Brás Varanda (Laboratório Editorial FCL-UNESP, 2015)
Considering the large volume of work that focuses on science communication today, this paper presents a case study taking a discursive perspective: it aims to understand how scientific images are constructed or, in other words, how the ways of seeing science objects are established. During our analysis, it is taken into account that advances in space exploration and in astronomy instrumentation have enabled the emergence of images of celestial objects with a level of unprecedented detail and also permitted, among other things, to photograph the Earth from an external and global perspective – at this point, a paradigm can be defined. This paradigm is focused as our main object in this paper. Moreover, through a historical and sociological perspective, it is considered that these developments coincide with the development of communication devices for widespread access, which released these images said to be scientific. Thus, mobilizing a theoretical model to approach imaginary positions, based on French discourse analyses, it is thought about how one of the most sacramental images in this collection was constructed: the Earth seen from space. The "Blue Marble" provides us a look at ourselves from a cosmic perspective, being thus invested with an ethical dimension, in addition to its technical, artistic or scientific dimensions.